Education Across the United Kingdom 1944-2017 Local Government, Accountability and Partnerships (Springer International Publishing, 2018)
This book provides a comprehensive understanding of how education has developed over the last 70 years within the United Kingdom. As education in Wales and Scotland continues to develop following increasing devolution, the contributors draw from personal accounts and practical experience to provide a comparison and evaluation of these differences. A critical stage in the history of education has been reached, particularly in light of the decision for Britain to leave the European Union: the authors explore the emergent fault lines and identify practical reforms. While this book will undoubtedly be of interest to educational historians, it will also be a valuable reference point for educationalists, practitioners and politicians. The contributors unpick the larger role of education in the United Kingdom and propose practical ways forward amid a time of crisis.